1998
DOI: 10.1007/s002030050554
|View full text |Cite
|
Sign up to set email alerts
|

A novel pink-pigmented facultative methylotroph, Methylobacterium thiocyanatum sp. nov., capable of growth on thiocyanate or cyanate as sole nitrogen sources

Abstract: The isolation and properties of a novel species of pink-pigmented methylotroph, Methylobacterium thiocyanatum, are described. This organism satisfied all the morphological, biochemical, and growth-substrate criteria to be placed in the genus Methylobacterium. Sequencing of the gene encoding its 16S rRNA confirmed its position in this genus, with its closest phylogenetic relatives being M. rhodesianum, M. zatmanii and M. extorquens, from which it differed in its ability to grow on several diagnostic substrates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
64
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 35 publications
3
64
0
Order By: Relevance
“…The genus Methylobacterium was first described by Patt et al (1976) and at the time of writing consists of the following 24 recognized species (http://www.bacterio.cict.fr/m/methylobacterium. html): Methylobacterium adhaesivum (Gallego et al, 2006), M. aminovorans (Urakami et al, 1993), M. aquaticum (Gallego et al, 2005a), M. chloromethanicum (McDonald et al, 2001), M. dichloromethanicum (Doronina et al, 2000), M. extorquens (Bousfield & Green, 1985), M. fujisawaense (Green et al, 1988), M. hispanicum (Gallego et al, 2005a), M. isbiliense (Gallego et al, 2005c), M. jeotgali (Aslam et al, 2007), M. lusitanum (Doronina et al, 2002), M. mesophilicum , M. nodulans (Jourand et al, 2004), M. organophilum (Patt et al, 1976), M. oryzae (Madhaiyan et al, 2007), M. podarium (Anesti et al, 2004), M. populi (Van Aken et al, 2004), M. radiotolerans , M. rhodesianum (Green et al, 1988), M. rhodinum , M. suomiense (Doronina et al, 2002), M. thiocyanatum (Wood et al, 1998), M. variabile (Gallego et al, 2005b) and M. zatmanii (Green et al, 1988). Here, we provide a detailed taxonomic characterization of a Methylobacterium-like bacterial strain, PMB02 T , which was isolated from a tree leaf.…”
mentioning
confidence: 99%
“…The genus Methylobacterium was first described by Patt et al (1976) and at the time of writing consists of the following 24 recognized species (http://www.bacterio.cict.fr/m/methylobacterium. html): Methylobacterium adhaesivum (Gallego et al, 2006), M. aminovorans (Urakami et al, 1993), M. aquaticum (Gallego et al, 2005a), M. chloromethanicum (McDonald et al, 2001), M. dichloromethanicum (Doronina et al, 2000), M. extorquens (Bousfield & Green, 1985), M. fujisawaense (Green et al, 1988), M. hispanicum (Gallego et al, 2005a), M. isbiliense (Gallego et al, 2005c), M. jeotgali (Aslam et al, 2007), M. lusitanum (Doronina et al, 2002), M. mesophilicum , M. nodulans (Jourand et al, 2004), M. organophilum (Patt et al, 1976), M. oryzae (Madhaiyan et al, 2007), M. podarium (Anesti et al, 2004), M. populi (Van Aken et al, 2004), M. radiotolerans , M. rhodesianum (Green et al, 1988), M. rhodinum , M. suomiense (Doronina et al, 2002), M. thiocyanatum (Wood et al, 1998), M. variabile (Gallego et al, 2005b) and M. zatmanii (Green et al, 1988). Here, we provide a detailed taxonomic characterization of a Methylobacterium-like bacterial strain, PMB02 T , which was isolated from a tree leaf.…”
mentioning
confidence: 99%
“…It includes strictly aerobic, Gram-negative, rod-shaped, pink-pigmented, facultatively methylotrophic (PPFM) bacteria, which can grow on single carbon compounds such as formate, formaldehyde and methanol as the sole source of carbon and energy, as well as on a wide range of multi-carbon growth substrates (Green, 2001). At the time of writing, the genus comprises 20 recognized species (Patt et al, 1976;Bousfield & Green, 1985;Green et al, 1988;Urakami et al, 1993;Wood et al, 1998; Doronina et al, 2000Doronina et al, , 2002 McDonald et al, 2001;Van Aken et al, 2004;Jourand et al, 2004; Gallego et al, 2005a, b, c), with Methylobacterium organophilum as the type species (Patt et al, 1976).Members of the genus Methylobacterium are ubiquitous in terrestrial habitats (Green & Bousfield, 1981, including soil, dust, freshwater, tap water systems, lake sediments, leaf surfaces and nodules, rice grains and air, and as contaminants in various products and processes. The PPFM bacteria are strict aerobes and can be isolated from almost any freshwater environment where some dissolved oxygen exists, e.g.…”
mentioning
confidence: 99%
“…Methylobacterium strains produce carotenoid pigment and bacteriochlorophyll in their cells, and they belong to a group of aerobic bacteriochlorophyll-containing (ABC) bacteria (Hiraishi and Shimada, 2001). Currently, the genus Methylobacterium consists of 14 valid species, Methylobacterium extorquens (Bousfield and Green, 1985), Methylobacterium rhodesianum, Methylobacterium zatmanii and Methylobacterium fujisawaense (Green et al, 1988), Methylobacterium aminovorans (Urakami et al, 1993), Methylobacterium thiocyanatum (Wood et al, 1998), Methylobacterium dichloromethanicum (Doronina et al, 2000), Methylobacterium chloromethanicum (McDonald et al, 2001), Methylobacterium suomiense, and Methylobacterium lusitanum (Doronina et al, 2002). The taxonomic study based on phenotypic properties (Green and Bousfield, 1982) showed that Methylobacterium species were divided into two physiological groups.…”
mentioning
confidence: 99%
“…1), they are likely to be the same strain. Compared to reference data of phylogenetic analysis (Doronina et al, 2002;Urakami et al, 1993;Wood et al, 1998), JCM 2833 T is thought to be the authentic type strain. Based on these facts, it is regarded that DSM 760 T had been mislabeled.…”
mentioning
confidence: 99%